Retrospective study of disease incidence and other clinical conditions diagnosed in owned dogs in Delta State, Nigeria - Shima, Kundu F.; Tion, Terzungwe M.; Mosugu, Idusiye J.; Apaa, Ternenge T. (Journal of Advanced Veterinary and Animal Research, 2015)
In Nigeria, knowledge on the epidemiology of diseases of dogs is limited. A retrospective study of data from clinical records of six veterinary clinics was undertaken to determine the incidence of disease in owned dogs in Delta State, Nigeria from 2012 to 2014. Association between the diagnosed diseases and the studied variables was explored using Chi-Squared test statistics. This study revealed that most of the conditions presented to the veterinary clinics were preventable. Thirty-one (31) clinical conditions were diagnosed from 571 cases recorded, involving nonspecific (21.6%), infectious (70.9%; P=0.001) and non-infectious (7.5%) diseases. The most occurring clinical conditions comprised helminthoses (21.4%), mange (10.5%), parvovirosis (8.4%), babesiosis (7.9%), septicemia (7.2%), gastroenteritis (7.0%), myiasis (7.0%), trauma (6.3%), poisoning (6.0%), ectoparasitism (3.7%), ascites (2.5%), dermatitis (2.3%), aural hematoma (1.2%), and orchitis (1.1%). Disease incidence was highest in Alsatian (40.3%), mixed/cross (33.1%), Rottweiler (7.0%) and toy breeds (4.6%). Details on the least occurring diseases and the association between disease and the studied variables are given. The outcomes demonstrate the prevalence of the clinical conditions diagnosed, inadequate husbandry and veterinary care accorded to owned dogs in the State. Education of dog owners on preventive measures is paramount in alleviating some of these health problems. http://dx.doi.org/10.5455/javar.2015.b115